Transformasi Digital Sebagai Implementasi Praktis Ideologi Berkemajuan Muhammadiyah - Oka Ediansa; Panggah Widiandana; Oman Fathurohman (Universitas Majalengka, 2025)
Digital transformation has become inevitable for religious organizations amid technological disruption and the COVID-19 pandemic. This study analyzes how digital transformation embodies Muhammadiyah's progressive ideology as a practical implementation of tajdid (renewal) and islah (reform). Using a qualitative approach based on literature review and thematic content analysis, the research synthesizes 22 recent scholarly references (2021–2025) relevant to digital da’wah, Islamic education, and Muhammadiyah organizational management. The analysis identifies three main themes: (1) digital da’wah through progressive-digital models, youth creative content, and social media; (2) Islamic education with digital literacy integration and value internalization in the disruption era; (3) sharia finance based on technology applications and shariah governance. Findings confirm that digital transformation strengthens Muhammadiyah's relevance in the Society 5.0 era, despite challenges of discourse contestation and ritual disruption. This study contributes to the discourse on technology-based Islamic religious education, with recommendations for developing integrative AI and big data curricula.